(untitled) (Anclajes, 2026)
Juan Pablo Riveros’s Libro del Frío (2000) establishes a relationship between poetry and photographic imagery to represent the human journey across the geography of the Antarctic continent. The poetic voice acts as a pseudo-chronicler, rescuing and reconstructing Admiral Richard E. Byrd’s journal, Alone (1938). The verses recreate unique scenarios and events, while the photographic images serve as a vehicle for recording these experiences. The work introduces dramatic moments from the American aviator’s stay in Antarctica, interwoven with the experiences of other travelers, in an exercise of survival. Crafted as an artist’s book, the work constructs a trajectory that progresses from the blackness of the Iberian Peninsula to the whiteness of the snow, emphasizing the introspective nature of the poetic self. This construction lends the volume a syncopated air that speaks to the journey, human resilience, and humanity’s cosmic connection to its environment.